The Road Not Taken: Neural Correlates of Decision Making in Orbitofrontal Cortex - Steiner, Adam P.; Redish, A. David (Frontiers in Neuroscience, 2012)
Empirical research links human Orbitofrontal Cortex (OFC) to the evaluation of outcomes during decision-making and the representation of alternative (better) outcomes after failures. When faced with a difficult decision, rats sometimes pause and turn back-and-forth towards goals, until finally orienting towards the chosen direction. Neural representations of reward in rodent OFC increased immediately following each re-orientation, implying a transient representation of the expected outcome following self-initiated decisions. Upon reaching reward locations and finding no reward (having made an error), OFC representations of reward decreased locally indicating a disappointment signal that then switched to represent the unrewarded, non-local, would-have-been rewarded site. These results illustrate that following a decision to act, neural ensembles in OFC represent reward, and upon the realization of an error, represent the reward that could have been.